Identification of Isoflavonoids in Wood Residue from Swartzia laevicarpa, Dipteryx odorata, and Andira parviflora - Garcia, M. G.; Nascimento, Claudete Catanhede; Ferreira, Antonio Gilberto; Lima, M. P. (Chemistry of Natural Compounds, 2018)
The industrial procesing of wood generates large amounts of residues that should be adequately managed. We identify methods to gain value wood rejects through phytochemical studies in three species of Fabaceae. Eight isoflavonoids were identified: 3′-hydroxy-7,8,4′,5′-tetramethoxypterocarpan from Swartzia laevicarpa; 8-O-methylretusin, cladrastin, 7,3′-dihydroxy-8,4′-dimethoxyisoflavone, and novel 7,3′-dihydroxy-5,6,4′trimethoxyisoflavone from Dipteryx odorata. In residues from Andira parviflora were identified genistein, biochanin A and 7,5′,6′-trihydroxy-4′-methoxyisoflavan. These compounds explain the natural resistance of these three timber species to xylophogous fungi. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.